Analysis of Civil Evidence Principles in The Ownership of Non-Fungible Token Assets - Maulana, Muhammad Asrul; Muharram, Fajar; Fajri, Kharisma Fatmalina (MultiTech Publisher, 2024)
This research aims analysis of the civil evidentiary principle, ownership of Non-Fungible Token assets can be proven through documents showing transfers from the previous owner to the current owner, as well as other evidence supporting the validity of the transaction. However, because NFT technology is still new and not fully legally recognized, further analysis is still needed to determine the appropriate mode of proof in this context. This study uses a normative method with a statutory approach (statute approach), as well as an analytical approach (analytical approach). The results of this study are to determine the principle of audi et alteram partem, the principle of ius curia novit, the principle of nemo testis indoneus in propria causa, the principle of ne ultra petita, the principle of de gustibus, non est disputandum, the principle of nemo plus juris transferre potest quam ipse habet on non-asset ownership Fungible Tokens. The principle of audi et alteram partem, which ensures that all parties have the right to be heard, upholds fairness in NFT ownership disputes by guaranteeing that each side has an opportunity to present their case.